Sosialisasi Gerakan Gemar Menabung (GEMABUNG) Sejak Dini Dan Meningkatkan Kreativitas Dengan Membagikan Celengan Bagi Anak-Anak SD Osiloa Tarus Kupang - Bau Mau, Ignatia Thomasita (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Socialization is an important method in the educational process, where the aim is to provide an understanding of a concept or practice to individuals or community groups. One example of relevant socialization is regarding the importance of saving in financial management. Saving is an activity that involves setting aside a certain amount of money over a certain period of time for future use. The importance of understanding finances does not only apply to adults or parents, but is also important for young children. Therefore, it is important to provide understanding and form good habits from an early age that can be useful in the future. The aim of this savings socialization activity is to train elementary school children in setting aside money for savings. The participants in this activity were children from Osiloa Tarus Elementary School aged between nine and ten years. The main strategy in this activity is to provide understanding about saving to young children. In this learning process, we use intermediary media, such as piggy banks, to train children's knowledge and creativity. It is hoped that conveying knowledge about saving combined with activities involving creativity will facilitate children's understanding of this concept.